RELATIONSHIP OF ADIPONECTIN LEVEL WITH LIPID PROFILE IN TYPE-2 DIABETIC MEN WITH CORONARY HEART DISEASE - Durrani, Sadaf; Shah, Jasmin; Khan, Mudassir Ahmad; Jan, Muhammad Rasul (Journal of Ayub Medical College Abbottabad, 2015)
Background: Cerebro-vascular disease is a commonest long term complication of type-2 diabetes mellitus. The study was done to determine concentration of serum adiponectin and lipid profile in type-2 diabetic men with coronary heart disease (CHD) in the region of Khyber Pakhtunkhwa (KPK), and to find possible relationship between them. Methods: This was a cross-sectional study comprising of randomly selected thirty six healthy adult males and thirty six type-2 diabetic males with coronary heart disease. Their fasting blood samples were analysed for serum adiponectin, fasting blood glucose, glycosylated haemoglobin and lipid profile which included total cholesterol (T-C), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). The relationship of adiponectin with other variables in type-2 diabetic men with coronary heart disease was determined with Pearson correlations coefficient (r). Results: Type-2 diabetic males with coronary heart disease when compared to healthy males showed significantly low levels of serum adiponectin (p=<0.001) and HDL-C (p=<0.001) and significantly high level of FBG (p=<0.001), HbA1c (p=<0.001), TC (p=<0.05), TG (p=<0.05) and LDL-C (p=<0.05). Serum adiponectin level showed a significant negative correlation with FBG (r = -0.332; p= 0.04), HbA1c (r = -0.818; p=<0.01) and TG (r = -0.640; p=<0.01) in type-2 diabetic men with coronary heart disease. Adiponectin showed a significant positive association with HDL-C in controls (r = 0.948; p=<0.01) and patients of type-2 diabetes with CHD (r = 0.650; p=<0.01). Conclusion: Serum adiponectin concentration is markedly decreased in patients of type-2 diabetes with coronary heart disease. Hypoadiponectinemia is related with deranged lipid profile, i.e., high TG and low HDL-C levels in type-2 diabetic men with CHD. Moreover, adiponectin is associated positively with HDL-C and negatively with HbA1c and TG levels in the studied population. Keywords: Adiponectin, Lipid profile, Type-2 diabetes mellitus, Coronary heart disease